2018
DOI: 10.1177/0963721418800030
|View full text |Cite
|
Sign up to set email alerts
|

On How to Be Flexible (or Not): Modulation of the Stability-Flexibility Balance

Abstract: Defining Stability and Flexibility Stability is characterized by goal maintenance and goal shielding, thereby preventing interference from distractors. Flexibility is a consequence of reduced goal maintenance and shielding, resulting in an increased ability to switch actions and thoughts to changing task 800030C DPXXX10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
166
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 41 publications
9
166
0
Order By: Relevance
“…However, our results showed the opposite pattern; not only did we not find an advantage in inhibition, but our data revealed a disadvantage in this regard. A plausible explanation for this finding might be accounted for by the stability-flexibility dilemma (Dreisbach & Fröber, 2019;Goschke, 2000Goschke, , 2013. In brief, the executive cognitive system has a limited amount of resources that can be allocated in order to achieve an effective adaptation in an environment in constant change.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed the opposite pattern; not only did we not find an advantage in inhibition, but our data revealed a disadvantage in this regard. A plausible explanation for this finding might be accounted for by the stability-flexibility dilemma (Dreisbach & Fröber, 2019;Goschke, 2000Goschke, , 2013. In brief, the executive cognitive system has a limited amount of resources that can be allocated in order to achieve an effective adaptation in an environment in constant change.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, being in a 70 positive or negative mood may alter what a person believes the requirements and payoffs of a 71 task to be (e.g., answering email can seem easier when we are in a good mood). Research has 72 demonstrated both forms of affective influence in the lab, showing that cognitive control varies as 73 a function of affective experiences evoked by the incentives for performancethose integral to 74 performance evaluation (i.e., performance-contingent rewards; e.g., Krebs et al, 2010;Locke & 75 Braver, 2008; Padmala & Pessoa, 2011; for reviews see: Botvinick & Braver, 2015;Parro et al, 76 2018)and as a function of affective experiences evoked by factors unrelated (incidental) to task 77 performance, for instance those that induce a particular mood state (i.e., positive mood induction 78 or performance non-contingent rewards; e.g., Dreisbach & Goschke, 2004;van Steenbergen, 79 Band, Hommel, Rombouts, & Nieuwenhuis, 2015; for reviews see: Inzlicht et al, 2015;Pessoa, 80 2008;Dreisbach & Fröber, 2018). While a number of such influences of affect on control 81 allocation have been documented (see Table 1 for a non-exhaustive overview of the empirical 82 findings), the mechanisms by which these influences occur remain mysterious.…”
Section: Abstract 23mentioning
confidence: 99%
“…C) Positive mood (high utility discounting) increases the switch cost in reaction times and in error rates. directing information processing (Dreisbach & Fischer, 2012;Dreisbach & Fröber, 2018;Inzlicht 358 et al, 2015), normative theories of cognitive control have largely overlooked affect's role in 359 control allocation. In this study, we leveraged a computational implementation of the EVC theory 360 (Lieder et al, 2018;Musslick et al, 2015;Shenhav et al, 2013) to simulate several candidate 361 mechanisms through which cognitive control can be influenced by integral affect (e.g., 362…”
Section: Figure 5 Effects Of Control Costs On the Expected Value Of mentioning
confidence: 99%
See 2 more Smart Citations